PENGARUH SLACK RESOURCES, MEDIA EXPOSURE DAN SENSITIVITAS INDUSTRI TERHADAP PENGUNGKAPAN CORPORATE SOCIAL RESPONSIBILITY (CSR) - Vianca Angela Tiono; Hendra Wijaya; Peggy Delita Merida (JURNAL ILMIAH MAHASISWA AKUNTANSI, 2022)
At present, almost every company or organization only cares about the competition it faces and social and environmental problems. Therefore, the risk that can occur is damage to the environment and the company's internal activities that will have an impact on the community. Therefore, companies need to have a Corporate Social Responsibility (CSR) streak, even though CSR companies are voluntary, but this creation is needed. The dependent in this study is Corporate Social Responsibility (CSR) using the GRI G4 standard as measured by the total items. The company variable is divided by the number of CSR items by the company as many as 91 CSR items. The independent variable used in this study is the slack resources variable, the second variable is media exposure and the third variable is industry sensitivity then assisted by a control variable, namely profitability (ROA), size firm (SIZE) and leverage (DAR). The companies that are the object of this research are mining, energy, chemical, pharmaceutical, cosmetic, food and beverage companies listed on the IDX for the 2017-2019 period. The sample was selected by purposive sampling method. Data analysis was performed using multiple linear regression. The results of the analysis show that slack resources and industrial sensitivity have no effect on the use of CSR, while media exposure has a significant positive effect on CSR